PERBANDINGAN METODE DOUBLE EXPONENTIAL SMOOTHING BROWN DAN HOLT DALAM MERAMALKAN KEBUTUHAN ENERGI LISTRIK SEKTOR BISNIS (Studi Kasus: PT. PLN (PERSERO) ULP Manokwari Kota) - Prita Larasati Prita Larasati; Esther Ria Matulessy; Nurhaida Nurhaida (Jurnal Natural, 2024)
Electric energy forecasting for the business sector is one of the solutions made to predict the need for electrical energy, especially the business sector, which is increasing every period. The purpose of this research is to forecast the electrical energy demand of the business sector to predict events that will occur in the future using mathematical models to minimize unwanted risks. Based on the data plot in the form of a linear trend and the research objectives, a comparison of the Brown and Holt double exponential smoothing methods is used in forecasting the electrical energy demand of the Manokwari City business sector to obtain the best model for the period August 2023 to July is 2024. The result of this study is to compare the best model obtained from the two models, namely Holt's double exponential smoothing with a forecasting model using parameters and with MAD value of , MSE value of , and MAPE value of .